"Diet in the Etiopathogenesis of IBD: Is There A Culinary Culprit?". Issue 1 (16th January 2020) - Issokson, Kelly
Lay Summary: Research suggests that diet plays a role in the development of inflammatory bowel disease (IBD). Eating more fiber, omega-3 fatty acids, and limiting food additives may lower risk. More research is needed to better understand diet factors that may protect against IBD.